RNA helicase DDX3 maintains lipid homeostasis through upregulation of the microsomal triglyceride transfer protein by interacting with HNF4 and SHP - Tsai, Tsung-Yuan; Wang, Wei-Ting; Li, Hao-Kang; Chen, Wei-Ju; Tsai, Yu-Hong; Chao, Chi-Hong; Lee, Yan-Hwa Wu (My University, 2017)
Multifunctional RNA helicase DDX3 participates in HCV infection, one of the major causes of hepatic steatosis. Here, we investigated the role of DDX3 in hepatic lipid metabolism. We found that HCV infection severely reduced DDX3 expression. Analysis of intracellular triglyceride and secreted ApoB indicated that lipid accumulations were increased while ApoB secretion were decreased in DDX3 knockdown HuH7 and HepG2 cell lines. Down-regulation of DDX3 significantly decreased protein and transcript expression of microsomal triglyceride transfer protein (MTP), a key regulator of liver lipid homeostasis. Moreover, DDX3 interacted with hepatocyte nuclear factor 4 (HNF4) and small heterodimer partner (SHP), and synergistically up-regulated HNF4-mediated transactivation of MTP promoter via its ATPase activity. Further investigation revealed that DDX3 interacted with CBP/p300 and increased the promoter binding affinity of HNF4 by enhancing HNF4 acetylation. Additionally, DDX3 partially relieved the SHP-mediated suppression on MTP promoter by competing with SHP for HNF4 binding which disrupted the inactive HNF4/SHP heterodimer while promoted the formation of the active HNF4 homodimer. Collectively, these results imply that DDX3 regulates MTP gene expression and lipid homeostasis through interplay with HNF4 and SHP, which may also reveal a novel mechanism of HCV-induced steatosis.